2007
DOI: 10.1152/ajpcell.00388.2006
|View full text |Cite
|
Sign up to set email alerts
|

Methoxyflavones protect cells against endoplasmic reticulum stress and neurotoxin

Abstract: O. Methoxyflavones protect cells against endoplasmic reticulum stress and neurotoxin. Enhanced endoplasmic reticulum (ER) stress leads to cell death in various pathophysiological situations. During a search for compounds that regulate ER stress, we identified methoxyflavones, a group of flavonoids, as strong protective agents against ER stress. Analysis in mouse insulinoma MIN6 cells revealed that methoxyflavones mildly activated the eukaryotic initiation factor 2␣ and nuclear factor erythroid 2-related factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 38 publications
4
50
0
Order By: Relevance
“…In addition, Kaser et al 7) reported that the transcription factor X-box binding protein 1 (XBP1), which is an important key to ER stress response, is involved in the genetic risk of onset of IBD in humans. These findings suggest a possible correlation between IBD and ER stress.We reported that dantrolene, an antagonist of ryanodine receptors in the ER, and some antioxidants such as a-tocopherol, partly prevented tunicamycin-induced cell death in F9 homocystein-induced ER protein null cells.8) Using this cell line, our group and others have reported that 103 plantderived compounds 9,10) and 200 synthetic compounds including dibenzoylmethane (DBM) derivatives, 11) carbazole derivatives, 12) and pyrimidine derivatives were screened previously, and some DBM derivatives improved cell viability after tunicamycin treatment at a level similar to that achieved by dantrolene in F9 Herp null cells.11) However, it remains unclear whether DBM derivatives that have protective effects against ER stress are effective against colitis.Nuclear factor kB (NF-kB) is a dimeric transcription factor that induces the expression of genes involved in the inflammatory process. Activation of NF-kB has been observed in the mucosa of patients with ulcerative colitis, 13) and butyrate has been shown to inhibit NF-kB activation in lamina propia macrophages of patients with ulcerative colitis.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, Kaser et al 7) reported that the transcription factor X-box binding protein 1 (XBP1), which is an important key to ER stress response, is involved in the genetic risk of onset of IBD in humans. These findings suggest a possible correlation between IBD and ER stress.We reported that dantrolene, an antagonist of ryanodine receptors in the ER, and some antioxidants such as a-tocopherol, partly prevented tunicamycin-induced cell death in F9 homocystein-induced ER protein null cells.8) Using this cell line, our group and others have reported that 103 plantderived compounds 9,10) and 200 synthetic compounds including dibenzoylmethane (DBM) derivatives, 11) carbazole derivatives, 12) and pyrimidine derivatives were screened previously, and some DBM derivatives improved cell viability after tunicamycin treatment at a level similar to that achieved by dantrolene in F9 Herp null cells.11) However, it remains unclear whether DBM derivatives that have protective effects against ER stress are effective against colitis.Nuclear factor kB (NF-kB) is a dimeric transcription factor that induces the expression of genes involved in the inflammatory process. Activation of NF-kB has been observed in the mucosa of patients with ulcerative colitis, 13) and butyrate has been shown to inhibit NF-kB activation in lamina propia macrophages of patients with ulcerative colitis.…”
mentioning
confidence: 90%
“…8) Using this cell line, our group and others have reported that 103 plantderived compounds 9,10) and 200 synthetic compounds including dibenzoylmethane (DBM) derivatives, 11) carbazole derivatives, 12) and pyrimidine derivatives were screened previously, and some DBM derivatives improved cell viability after tunicamycin treatment at a level similar to that achieved by dantrolene in F9 Herp null cells.…”
mentioning
confidence: 98%
“…Methoxyflavone, a group of flavonoids, is also identified as a strong ER stress modulator. Pretreatment of mice with tangeretin, a methoxyflavone, enhanced the expression of GRP78 and HO-1 in renal tubular epithelium and prevented tunicamycininduced cell death (Takano et al, 2007).…”
Section: Chemical Upr Modulatorsmentioning
confidence: 99%
“…One hundred and three plant-derived compounds, including flavonoids and stilbenoids, and 300 synthetic compounds, including dibenzoylmethane (DBM) derivatives, carbazole derivatives, and pyrimidine derivatives were analyzed for the protective effects against ER stress in F9 Herp null cells, as previously described (8 (12). Dantrolene (Dan), carbazole, N-acetyl cysteine (NAC), Tm, Tg, bradykinin (BK), and nifedipine (Nif) were obtained from Sigma.…”
Section: Compounds and Cell Viability Assaysmentioning
confidence: 99%
“…We previously reported that dantrolene, an antagonist of ryanodine receptors in the ER, significantly prevented Tm-induced cell death in F9 Herp null cells (8). Using this agent as a positive control, 103 plant-derived compounds and 300 synthetic compounds were screened in F9 Herp null cells treated with Tm.…”
Section: Prevention Of Tm-induced Cell Death By Carbazole Derivativesmentioning
confidence: 99%